Social Value in Mobile Game - Budi Sriherlambang; Liliek Adelina Suhardjono (Bina Nusantara University, 2017)
As technology improves, more and more aspects of games move closer to the human life and activities, including the way people interact and socialize with each other within their community. Pokemon Go is one of those games that utilize the social aspect of its players. This paper aims to maintain that in the process of playing Pokemon Go, the player greatly involve in a social engaging experience, and it is all possible with the help from the visual aid from the visual communication design.Â